Routine immunization intensification, vaccination campaigns, and measles transmission in Southern Nigeria - Niket Thakkar; Avuwa Joseph Oteri; Kevin A. McCarthy (PLoS ONE, 2026)
In this paper, we compare—in terms of their estimated effects on disease transmission—Southern Nigeria’s large-scale measles vaccination campaigns since 2010 to a unique, more targeted routine immunization intensification that happened in 2019. A main focus of the discussion throughout is that quantifying intervention impact in real epidemiologies requires us to disentangle competing, dynamic sources of immunity, including unreported infection. To address this inference challenge, we create a collection of state-level, stochastic transmission models capable of estimating underlying measles susceptibility based on surveillance and survey data. Leveraging these models, we find that the 2019 intensification, despite being restricted in scale to children under 2 years-old, had an effect on transmission comparable to the region’s larger vaccination campaigns targeting children up to 5. This implies that vaccines delivered in that effort were more than twice as likely to reach a susceptible child.